2021
DOI: 10.1055/s-0041-1723014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Biological Sex on Complications, Lengths of Stay, Readmission Rates, and Costs of Care Following Primary Total Knee Arthroplasty

Abstract: The impact of gender on total knee arthroplasty (TKA) postoperative complications, readmission rates, and costs of care has not been often evaluated. Therefore, the purpose of this study was to investigate which sex had higher rates of: (1) medical complications; (2) implant complications; (3) lengths of stay (LOSs); (4) readmission rates; and (5) costs after TKA. A query was performed using an administrative claims database from January 1, 2005, to March 31, 2015. Patients who had TKAs were identified using I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The supercomputer houses the records of more than 150 million patients between a private payor database and the Medicare claims database. The time frame provided within the Medicare claims of the PearlDiver platform is analyzed; it has been utilized in other studies using the same database 14 15 16 17 18 19) . Due to the number of patient records available within the database, PearlDiver has been used extensively for orthopaedic-related research within all disciplines of orthopaedic surgery.…”
Section: Methodsmentioning
confidence: 99%
“…The supercomputer houses the records of more than 150 million patients between a private payor database and the Medicare claims database. The time frame provided within the Medicare claims of the PearlDiver platform is analyzed; it has been utilized in other studies using the same database 14 15 16 17 18 19) . Due to the number of patient records available within the database, PearlDiver has been used extensively for orthopaedic-related research within all disciplines of orthopaedic surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Based on previously published studies, 8 , 9 we included several covariates that have been shown associated with our study outcomes: age (<45, 45–64, and 65+ years), sex, neighborhood income quintile, 19 rural versus urban/suburban residence, 20 comorbidity (Deyo-Charlson Comorbidity Index derived from health care use during the 2 years preceding the index surgery and grouped as 0, 1, 2, 3+), 21 surgery type (inpatient vs outpatient), and surgical anatomical site.…”
Section: Methodsmentioning
confidence: 99%
“…Studies following major elective orthopedic surgery, such as joint arthroplasty, show quality indicators are influenced by multiple factors such as age, sex, insurance status, and comorbidity. 8 , 9 One additional potential factor that has received less attention is patients’ use of health services prior to surgery. The few studies that have considered it have been limited to highly selected populations (i.e., 65+ years, US military), single institutions, or specific types of surgery.…”
Section: Introductionmentioning
confidence: 99%
“…PearlDiver is a database which contains the records of over 150 million Medicare and private payor patients. The years analyzed within this investigation are those which are provided within the Medicare claims from the PearlDiver database, and has also been used in other previously published studies using the same platform [13][14][15][16]. Due to its extensive population size, the database has been used extensively for orthopedic-related research.…”
Section: Data Sourcementioning
confidence: 99%